Theoretical aspects of agrarian enterprises’ competitiveness management - Поліщук, В. А. (Scientific Progress & Innovations, 2017)
The notion of competition, competitiveness of enterprises, the ways of its improving, and the factors affecting competitiveness have been considered in the article. The system of measures to raise the efficiency of management have been suggested. The emphasis is placed on the fact that the competitiveness problem is global and influences many aspects of both economic and social policy of the state, on the one hand, and on the other hand, it is related to the interests of all citizens as consumers of goods.